Pengaruh E-WOM dan Inovasi Produk terhadap Keputusan Pembelian Produk Revlon di Kabupaten Jombang - Anggraeni, Ratna Fransiska; Aminah, Siti (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Revlon is a cosmetic company from the United States which was founded in 1932 by Charles Revson and Joseph Revson with a chemist Charles Lachman. For this reason, so that the product remains in demand by consumers, the purpose of this study is to determine and analyze the effect of E-WOM and product innovation on purchasing decisions for Revlon products in Jombang Regency. The research method used is a quantitative method by distributing questionnaires. The population in this study are female consumers who use Revlon products who live in Jombang Regency. The sample in this study used a purposive sampling technique with a total sample of 96 respondents. Data analysis technique uses PLS with SmartPLS 3.0 software. The results of this study indicate that E-WOM has a positive and significant influence on purchasing decisions and product innovation has a positive and significant influence on purchasing decisions. Keywords: E-WOM; Product Innovation; Buying decision